POLITENESS IN ENGLISH AND UZBEK LANGUAGES - Matluba Isoqjon qizi Turdieva; Raximbekova Hadicha Baxrombek qizi (Western European Studies, 2025)
This article provides a comparative analysis of politeness as a component of speech etiquette in English and Uzbek languages, highlighting the cultural and linguistic factors that influence expressions of politeness in both societies. Address forms, requests, expressions of gratitude and apology, and the overall tone used in both languages are especially highlighted. The analysis also demonstrates how politeness reflects cultural values and communication styles in English-speaking and Uzbek-speaking communities.
Keywords: Politeness; Speech Etiquette; English Language